2018
DOI: 10.1371/journal.pone.0208151
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of transport proteins in seven Bacteroides species

Abstract: The communities of beneficial bacteria that live in our intestines, the gut microbiome, are important for the development and function of the immune system. Bacteroides species make up a significant fraction of the human gut microbiome, and can be probiotic and pathogenic, depending upon various genetic and environmental factors. These can cause disease conditions such as intra-abdominal sepsis, appendicitis, bacteremia, endocarditis, pericarditis, skin infections, brain abscesses and meningitis. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 95 publications
1
32
0
Order By: Relevance
“…Moreover, pathways related to human diseases (such as cancer, infectious diseases, metabolic diseases, and neurosurgical diseases) are positively correlated with the abundance of Klebsiella found in this study were also supported by several other studies [49][50][51][52][53]. For Bacteroides, a common probiotic, the decrease of this kind of probiotic may cause dysbiosis of gut microbiota and leads to human health problem [54][55][56][57]. There are some other studies showed that Bacteroides intrinsically carries tetracycline and aminoglycoside resistance genes [58][59][60].…”
Section: Antibiotic Effects On the Genetic Level May Attribute To Micsupporting
confidence: 83%
“…Moreover, pathways related to human diseases (such as cancer, infectious diseases, metabolic diseases, and neurosurgical diseases) are positively correlated with the abundance of Klebsiella found in this study were also supported by several other studies [49][50][51][52][53]. For Bacteroides, a common probiotic, the decrease of this kind of probiotic may cause dysbiosis of gut microbiota and leads to human health problem [54][55][56][57]. There are some other studies showed that Bacteroides intrinsically carries tetracycline and aminoglycoside resistance genes [58][59][60].…”
Section: Antibiotic Effects On the Genetic Level May Attribute To Micsupporting
confidence: 83%
“…Kanwal et al also observed similar trends, in which the levels of Bacteroidaceae family and Bacteroides genus were increased in mice treated with antibiotics (clindamycin and metronidazole). To our knowledge, Bacteroides contain both probiotic and potentially pathogenic species . On the one hand, Bacteroides with beneficial effects, such as B. vulgatus and B. dorei , could suppress the proinflammatory response by ameliorating endotoxemia and gut microbiota lipopolysaccharide levels in atherosclerosis‐prone mice .…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of all GI-tract microbiota consists of Gram-negative anaerobic bacteria, and Bacteroidetes species represent the most abundant Gram-negative anaerobes, outnumbering Escherichia coli in abundance by about 100 to 1 [3][4][5][6][7][8]14,15,[61][62][63][64]. Certain strains of Bacteroidetes species such as Bacteroides fragilis (B. fragilis), as a normal commensal microbe of the human GI-tract, are thought to be ordinarily beneficial to human health due to their multiple capabilities: (i) to biosynthesize useful metabolic co-factors and products such as polysaccharides, transport proteins, volatile fatty acids and other nutrients [9,14,47,62,74]; (ii) to cleave dietary fiber into digestible short-chain fatty acids (SCFAs) that include acetate, propionate, and butyrate [9,38,63,74]; (iii) to function in the maintenance, development and homeostasis of the host immune system [14,47,62,74,79]; (iv) to support immunomodulation and protection against pathogens including potentially pathogenic GI tract bacteria [9,14,29,63,79]; and (v) to support glucose homeostasis [8,9,13,63,69,72]. Conversely, when enterotoxigenic strains of B. fragilis or their array of secretory neurotoxins leak through normally protective biophysiological-mucosal barriers they can cause substantial inflammatory pathology sys-temically that can contribute to significant mortality and morbidity…”
Section: Overview: Human Gi-tract Microbiome and Bacteroides Fragilismentioning
confidence: 99%